Important Factors for Developing and Establishing ‘Long-term Relationships’ with the Customers/Clients - Visaria, Rachit (2010)
In an increasingly networked society where customers can interact easily with other customers and firms through social networks and other new media, the authors propose that managing customer relationship is essential to success of modern business.